2018
DOI: 10.1021/acsabm.8b00681
|View full text |Cite
|
Sign up to set email alerts
|

NIR-Responsive Copolymer Upconversion Nanocomposites for Triggered Drug Release in Vitro and in Vivo

Abstract: Light has several advantages as the stimulus for a triggered drug release. Currently, the applications of phototriggered drug-release devices (PDDs) are largely limited by two factors: the limited tissue penetration and detrimental effects caused by excitation light (ultraviolet or visible light). To address this disadvantage, this study developed nanocomposites based on upconversion nanoparticles (UC), which could convert near-infrared light to ultraviolet–visible light and trigger drug release. By loading UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…This approach allowed to release DOX which was coloaded with UCN within the micelle. [215] The drug release was consistent with the induction of cytotoxicity observed in MCF-7 breast cancer cells under NIR irradiation. This strategy was similarly applied for NIR-induced siRNA delivery.…”
Section: Disassembly Via Nir Photolysissupporting
confidence: 80%
See 1 more Smart Citation
“…This approach allowed to release DOX which was coloaded with UCN within the micelle. [215] The drug release was consistent with the induction of cytotoxicity observed in MCF-7 breast cancer cells under NIR irradiation. This strategy was similarly applied for NIR-induced siRNA delivery.…”
Section: Disassembly Via Nir Photolysissupporting
confidence: 80%
“…Lai et al reported fluorescein-loaded mesoporous silica nanoparticle (MSN) grafted with ONB-caged poly(N-isopropylacrylamide-co-acrylate) polymer on its porous surface. Under an ambient condition, its pores remained closed due to its randomly collapsed polymer brushes [ 207,208] HA polymer micelle DOX ONB [ 210] Polymer micelle-aptamer Sgc8 DOX ONB [ 211] Polymer tubisome DOX ONB (365) [ 209] UCN@polymer micelle DOX ONB (980) [ 212,215] Crosslinked polymer micelle DOX [2+2] Addition (254) [ 217] Polymer micelle DOX Coumarin (430) [ 213] NP aggregate Camptothecin 2-Nitroresorcinol (UV-vis) [ 214] UCN@siRNA siRNA ONB (980) [ 216] Liposome Gd(II) complex ONB (400) [ 205] Liposome Carboxyfluorescein ONB (365) [ 204] Polymer micelle Nile red ONB (365), BODIPY (470) [ 119,206] Gating mSiO 2 @Polymer -ONB [ 218] AuNS@mSiO 2 DOX ONB (980) [ 219] UCN@mSiO 2 Fluorescein ONB (980) [ 220] mSiO 2 Rhodamine Ru-S (455) [ 221] UCN@mSiO 2 DOX Ru-S (977) [ 222] ( Figure 9A). [218] However, under UV irradiation, they observed pore opening that allowed payload diffusion.…”
Section: Therapeutic Release Via Photolytic Gate Controlmentioning
confidence: 99%
“…In particular, oNB, coumarin and their derivatives are the most frequently used photolytic chromophores for UCNP‐assisted photolysis in NIR triggered drug delivery. For instance, Zou and co‐workers designed a NIR light‐triggered nanocomposites PEG–NMAB–PLA–UCNPs (PNP‐UC) to realize the photocontrollable release of DOX for cancer therapy ( Figure ) . Under NIR irradiation by a 980 nm laser, the oNB phototrigger was activated, PNP‐UC was dissociated and the DOX was released.…”
Section: Nir Light Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…d) In vivo antitumor activity and images of excised tumors after 26 d, scale bar, 2 cm. Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Nir Light Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…Under the irradiation of 980 nm NIR light, 2-nitrobenzyl group was triggered for its cleavage to release DOX. Compared with other UCNPs-based NIR responsive systems, this new nanocomposite has many advantages, such as high drug encapsulation efficiency, fast light responsiveness at low power density and less heating effect, showing potential in pharmaceutical and biomedical applications [ 119 ].…”
Section: Stimulus-responsive Systemsmentioning
confidence: 99%